PENINGKATKAN PUKULAN FOREHAND DAN BACKHAND MELALUI MEDIA DINDING PERMAINAN TENIS MEJA SISWA SMP NEGERI 8 PALOPO - Abdul Rahman (Jurnal Panrita, 2020)
This research is a classroom action research with 29 students as research subjects. The instrument used was a test instrument to improve learning outcomes of forehand and backhand in table tennis. The purpose of this study is to determine the learning improvement of Forehand and Backhand in table tennis games using wall mediumat the eight grade of Junior high school number 8 Palopo.Based on the research results, it can be concluded that in the pre-action activity 11 students (37.93%) are in the complete category and 18 students (62.07%) are in the incomplete category. In the implementation of Cycle I, there are 17 students (58.62%) in the complete category and 12 students (41.38%) in the incomplete category. Whereas in Cycle II it shows 26 students (89.66%) are in the complete category and 3 students (10.34%) are in the incomplete category. Based on the results obtained, it can be concluded that there is an improvement in learning outcomes for the ability to perform Forehand and Backhand in table tennis using wall medium in Class VIII Students of SMP Negeri 8 Palopo.